Research on the matching model of IoT features and network needs - Er-ling ZHOU; Yun LU; Hui XUE; Xing-hua ZHUANG (物联网学报)
On the one hand,the Internet of Things brings new opportunities for operators.On the other hand,it also poses a serious challenge to the operators' networks.In order to solve the problem that the development of Internet of Things (IoT) matches the network construction,the business characteristics of cellular Internet of Things are sorted out through the collection of external information and internal research,and it builds a matching model between cellular Internet of Things business characteristics and network construction needs,which provides input for network construction.